The role of indigenous knowledge systems in upholding marriages in Zimbabwe: a case study of Zaka district (2005-2016) - Muzvarwi, Fungai (Midlands State University, 2018)
This study examines the role of Indigenous Knowledge Systems, particularly love potions (mupfuhwira) in upholding marriages in Zaka district. Marriage institution has been and is still under crisis because of economic and social factors and this has triggered high divorce rate in Zimbabwe, as a whole. The purpose of this study is to highlight how love potions are helpful in sustaining marriages. The research has revealed reasons why people utilize love potions, names and types of love potions have also been identified. The experiences of the many of women interviewed for this study showed that, there are negative and positive results of using love potions. Factors for the little recognition or just, alternatives of love potions have been outlined in this study. Love potions have been regarded by Christians and others, as archaic and heathenish, and as a result, modern and holistic approaches such as counseling and praying have been used to uphold marriages. However, the study assesses whether these approaches are successful in upholding marriages compared to the use of love position, or are people really sticking to these or are secretly resorting to love potions. The findings of the research are that, both men and women make use of love potions, thereby nullifying the notion that women are the mere users of love potions. Also the study has found out that, people really use love potions to uphold their marriages, though they do not want to be known or exposed. The study suggests that, incorporating or integrating Indigenous Knowledge Systems in the marriage sector can help solve marital problems, thereby making marriage a lifetime commitment as was in the past.